PREIMAGINAL STAGES OF PANGULLIA NEA ROJAS, 2 0 0 6 (TRICHOPTERA: KOKIRIIDAE) OF CHILE (Acta Entomológica Chilena, 2022)
The larvae and pupae of the Chilean species Pangullia nea Rojas, are here described and illustrated. So the preimaginal States of genus Pangullia are recognised by first time. This preimaginal forms are compared to the descriptions of the New Zealand species of Kokiria miharo McFarlane, since Kokiriidae has mainly Australasian distribution and in the Neotropic occurs exclusively in the Chilean SubRegion.
Keywords: immature stages, Trichoptera, Kokiriidae, Pangullia, new record, Neotropical, Chile